NIGER DELTA DEVELOPMENT CRISIS AND INFRASTRUCTURAL PROVISIONS IN THE OIL PRODUCING AREAS OF NIGERIA, 2009-2017 - Rebecca Ginikanwa Nnamani,; Ezinwanne Ekekwe, Quentin Chukwuemeka Chukwu, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study interrogates the Niger Delta development crisis and infrastructural provisions in the oil producing areas of Nigeria, 2009-2017. Data were generated using the documentary and survey methods. Findings revealed that the federal government interventionist structures are products of ethnic power calculation and not only elitist in nature but also specifically designed to protect the oil and gas interest of the elites of the dominant ethnic groups. This largely explains why the agency is under the tight control of the Presidency and its commissioners, politically appointed (mainly members of the ruling party). Invariably, NDDC like its predecessor is constrained by the placement of politics before the development agenda of the region. The study calls for the Commission to carry out a comprehensive review of their projects to determine their status. Where contracts have been abandoned, contractors should be prosecuted to enable the commission recover advances to them. Where a contractor deliberately delays a job with intention of obtaining price variation, such contractor should be made to deliver on the old agreed price or the contract should be cancelled and re-awarded.